Desenvolvimento e caracterização de filmes e blendas poliméricas de quitosana, pectina e fécula de mandioca para revestimento em frutos - Costa, Tamara Lorena Eufrazio da (2018)
Non-biodegradable polymer materials from fossil sources have become a problem mainly due to the long degradation time of these materials in the environment. Thus, many studies have shown interest in the production and application of biopolymer films as functional materials in the most diverse areas. Especially due to its unique characteristics such as biocompatibility, biodegradability, non-toxicity, antimicrobial activity and easy production. In this sense, it becomes interesting and necessary to study biofilms from biopolymer blends. Therefore, the objective of this work is to develop and characterize edible biofilms produced by polymer blends, composed of natural polysaccharides, aiming their use as edible coatings for fruits, and to be used as a renewable source in partial replacement of films produced by synthetic polymers. For this purpose, seven polymer films were developed by the casting technique. The present work was carried out in two stages, in the first part were developed three individual films based on chitosan, pectin and cassava starch crosslinked with anhydrous citric acid PA. In the second part, the polymer blends were prepared from the blends of the individual polymer solutions forming four more films. The influence of the used plasticizer (glycerol), and the added crosslinking agent on cassava starch, was evaluated. The optical, morphological, mechanical, and barrier properties were evaluated, among others. The films showed homogeneous surfaces without phase separation, with intermediate values of the Water Vapor Permeability Rate for the blends in relation to the individual and statistically significant films at the 95% confidence level. The solubility values were lower in films containing chitosan due to their insolubility in water. For the values of contact angle and mechanical properties were not statistically improved with the polymer blend. All films had good luminosity with the exception of the chitosan / pectin blend which was more opaque with statistical difference for opacity due to the yellowish color of the chitosan powder. There was increase in the roughness of the films with addition of the crosslinking agent in cassava starch; however, the morphology of the individual films as well as of the blends was homogeneous and cohesive, indicating compatibility of the blends. The blends provided a reduction of water permeation rate without compromising their characteristics, but the best blends developed as an alternative of edible coatings for increasing the shelf life of fruits is that of chitosan / cassava starch